Spectrophotometeric Determination of Ponceau 4R in the Several Beverages Using Mixed Micelles after Cloud Point Extraction - Thani, Mohammed Z; Al-Ameri, Salam A. H; Sultan, Muntadhar Salih (Al-Nahrain Journal of Science, 2018)
Ponceau 4R(E124) is azo dye that is mostly used in some of food products such as soft drinks, beverages, jelly and ham. A simple and sensitive procedure is established for the determination of ponceau 4R using cloud point extraction (CPE). In order to get the optimum conditions for ponceau 4R extraction, various analytical factors such as pH media, nonionic surfactant TX-114 or Brij-56, cationic surfactant CPC and equilibration temperature was investigated. The linearity of calibration graph was above the range of 0.05-1.7 µg ml-1. The LOD and LOQ using TX-114 were based to be 0.025, 0.075 µg ml-1 whereas for Brij-56 were found as 0.062, 0.187 µg ml-1 respectively. The proposed procedure was successfully employed for ponceau 4R detection in several beverages samples